A Basic Understanding of Integrating Geophysical Hydrological and GIS Approach in Delineation of Artificial Recharge Site - Case Studies from Indian Sub-Continent - Rolland Andrade; Balamurugan Guru (Geography, Earth Science and Environment: Research Highlights Vol. 8, 2025)
The present study explores recharge Site Delineation through an Integrated Geophysical Hydrological and GIS Approach. Numerous government schemes have been implemented in recent times towards sustainable groundwater development and quality management through water harvesting and artificial recharge strategy development. Artificial recharge strategy has been adapted largely in such situations to augment the groundwater reserves by transferring the surface water to the aquifers during the monsoon months and using this water in the lean period. In groundwater studies, several geophysical methods have been deployed since late 1915, of which the electrical method has shown a wider approach and better applicability. Basically, there are two types of procedures involved in electrical resistivity survey, of which resistivity profiling is adopted to understand qualitatively the nature of the subsurface, whereas vertical resistivity sounding (VES) quantifies the resistivity variation with depth and thickness. All the case studies discussed in this paper pertain to different geological terrains, where the integrated approach of geophysical, hydro-geological and GIS studies have been implemented. The outcome of the integrated approach resulted in groundwater quality enhancement and sustenance. A similar strategy can be adopted at any given site in India as well as other countries to achieve effective outcomes in enhancing groundwater recharge and its sustenance.